Maternal and fetal outcome in second stage caesarean section: a retrospective study - Chandrashekhar, Anusha B.; Ramakrishnappa, Hemalata C.; Nagaraj, Rakshith; Iyengar, Swati L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: This study aims to observe the maternal and neonatal outcomes of caesarean delivery performed in the second stage of labor. Methods: This was retrospective observational study conducted at Cheluvamba hospital, Mysore medical college, Mysore, in the department of Obstetrics and Gynaecology. All second stage caesarean sections performed between January 2023 to June 2023 were analyzed in terms of incidence, indications of caesarean-section, intra-operative and postoperative complications, maternal and fetal outcome. Results: During the study period there were total 4194 deliveries. Out of this 1771 deliveries were done by caesarean section. Out of them 48 were 2nd stage caesarean sections contributing to 2.71% of total sections. Patwardhan method was used in 41.6% cases for delivery of deeply engaged head. Intra-operative complications were higher in terms of atonic pph (25%), hematuria (16.66 %). 14% cases had postoperative fever and 41.6% cases need prolonged catheterization. 20.83% babies required NICU admissions and neonatal death was 4.16%. Conclusions: Caesarean section in the 2nd stage of labour is associated with increased maternal and neonatal morbidity. A proper judgement is required by a skilled obstetrician to take a decision for caesarean section at full cervical dilatation.